PENINGKATAN HASIL BELAJAR SISWA PADA PEMBELAJARAN KIMIA MELALUI PENERAPAN MODEL PROBLEM BASED LEARNING PADA SISWA KELAS X DI SMAN 6 MATARAM - Nyoman Martha Jayanthi Lembayung; Oni Pahdianti; Rauhul Jannah (JURNAL ASIMILASI PENDIDIKAN, 2023)
The purpose of this research is to improve students' learning outcomes in chemistry subjects by using Problem-based learning model in class X students of SMAN 6 Mataram. This study used the method of Collaborative Classroom Action Research (PTK) which took place with three cycles, where each cycle included several steps, including planning, implementation, observation, and reflection. In this study, the subjects were students of class X6 SMAN 6 Mataram which amounted to 34 students. The results of the research obtained are Problem Based Learning learning model can improve students' cognitive learning outcomes in chemistry. This can be seen from the average value of students' cognitive learning outcomes and the percentage of classical learning completeness. The average value of students in the first cycle was 48.84 with a percentage of classical learning completeness of 20.50%, in cycle two the average value of students was 78.78 with a percentage of classical learning completeness of 88.2%, while in cycle three the average value of students was 87.66 with a percentage of classical learning completeness of 97%. This research is expected to form a new solution to solve problems in learning activities, especially in chemistry subjects.